Towards the Publication of The Transfer of Power Documents, 1961–69. Issue 1 (2nd January 2022) - Ankit, Rakesh
Abstract: This article attempts a pre-history of the publication of The Transfer of Power documents through the 1960s. In doing so, it: (1) throws light on the external reasons and internal motivations at play for this pivotal production; (2) presents the other options considered and the formula eventually followed; and (3) illustrates the method by which the officials, librarians and historians involved went about including, excluding and editing the documents concerned. Through it all, the article seeks to trace the timeline, tease out the creative tensions and tackle the political imperatives of this attempt to influence historiography on the original transfer of power. Drawing upon official archives behind the emergence of this archival corpus, it concludes its analyses of this exercise of the late 1960s by drawing parallels with the emotions of the late 1940s and finds that the pride and prejudice displayed then fed the principles and pragmatism exhibited now.